2011
DOI: 10.1371/journal.pone.0021111
|View full text |Cite
|
Sign up to set email alerts
|

p16INK4A Positively Regulates Cyclin D1 and E2F1 through Negative Control of AUF1

Abstract: BackgroundThe cyclin-D/CDK4,6/p16INK4a/pRB/E2F pathway, a key regulator of the critical G1 to S phase transition of the cell cycle, is universally disrupted in human cancer. However, the precise function of the different members of this pathway and their functional interplay are still not well defined.Methodology/Principal FindingsWe have shown here that the tumor suppressor p16INK4a protein positively controls the expression of cyclin D1 and E2F1 in both human and mouse cells. p16INK4a stabilizes the mRNAs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 43 publications
4
47
0
Order By: Relevance
“…9). Indeed, p16 also negatively regulates AUF1 post-transcriptionally (46), which could explain the key role of p16 in the activation of stromal fibroblasts. Therefore, either AUF1 up-regulation or p16 down-regulation will both lead to stromal fibroblast transactivation and the consequent promotion of metastasis.…”
Section: Discussionmentioning
confidence: 97%
“…9). Indeed, p16 also negatively regulates AUF1 post-transcriptionally (46), which could explain the key role of p16 in the activation of stromal fibroblasts. Therefore, either AUF1 up-regulation or p16 down-regulation will both lead to stromal fibroblast transactivation and the consequent promotion of metastasis.…”
Section: Discussionmentioning
confidence: 97%
“…Apoptosis Analysis by Annexin V/Flow Cytometry-Cells were either not treated or challenged with UV light (10 Jm Ϫ2 ), then harvested after 72 h, centrifuged, and stained by propidium iodide and Alexa Fluor 488 annexin V (Molecular Probes, Eugene, OR) as described previously (18).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, several lines of evidence indicate that p16 is overexpressed at both protein and mRNA levels in certain tumors, and this has been shown to be associated with poor prognosis (13,14). Furthermore, it became clear that p16 interacts with several proteins (15,16), and it also regulates the expression of different genes involved in various cellular processes (17,18). We have recently shown that p16 negatively regulates the expression of AUF1 through activating the turnover of its mRNA (18).…”
Section: P16mentioning
confidence: 99%
See 2 more Smart Citations